2012
DOI: 10.1111/j.1440-1797.2012.01592.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of the relationship between ACE I/D gene polymorphism and end‐stage renal disease in patients with diabetic nephropathy

Abstract: Our results indicate that D allele or DD homozygous is associated with the ESRD susceptibility in DN patients. However, more investigations are required to further this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 45 publications
(63 reference statements)
5
43
1
1
Order By: Relevance
“…Due to the influence of genetic factors and metabolic control in the pathogenesis of DN, its development varies among diabetic patients (31). The role of ACE I/D polymorphism in the development of DN to ESRD in T2DM patients has been demonstrated by a recent meta-analysis (32). In contrast, Manea et al (33) found a protective role for the D allele of ACE against diabetic nephropathy.…”
Section: Ace I/d Polymorphism: Onset and Progression Of Diabetic Nephmentioning
confidence: 99%
“…Due to the influence of genetic factors and metabolic control in the pathogenesis of DN, its development varies among diabetic patients (31). The role of ACE I/D polymorphism in the development of DN to ESRD in T2DM patients has been demonstrated by a recent meta-analysis (32). In contrast, Manea et al (33) found a protective role for the D allele of ACE against diabetic nephropathy.…”
Section: Ace I/d Polymorphism: Onset and Progression Of Diabetic Nephmentioning
confidence: 99%
“…Abbreviations: CI, confidence interval; OR, odds ratio relationship between susceptibility to DN and GST polymorphisms. Meta-analyses of several individual genetic variants in relation to DN have been performed previously, [25][26][27] but this is the first complete overview of the association between GST polymorphism and DN. An accurate estimation of this association provided by a meta-analysis could provide a better insight into the underlying pathogenetic mechanisms of DN.…”
Section: 20mentioning
confidence: 99%
“…2 DN includes Type-1 diabetic nephropathy (T1DN), due to Type-1 diabetes mellitus, and Type-2 diabetic nephropathy (T2DN) due to Type-2 diabetes mellitus. 3,4 Some investigations suggest that genetic factors might act with a key role in the susceptibility of DM developing into DN.…”
Section: Introductionmentioning
confidence: 99%